Simultaneous quadricipital tendon and contralateral patellar tendon rupture in a patient undergoing hemodialysis treated using hamstring autograft: A case report - Camilo A. Martínez; Juan D. Parra; Esteban Ortega; Hellen Y. Echeverry (Journal of Orthopaedic Reports)
Bilateral rupture of the knee extensor mechanism is a rare condition, typically occurring in patients with systemic comorbidities such as chronic kidney disease and those undergoing hemodialysis. We present the case of a 45-year-old male who sustained a quadriceps tendon rupture with a contralateral patellar tendon rupture following a fall. The patient was treated with primary repair and augmentation using hamstring autografts in both knees. The surgical technique involved transosseous sutures and graft augmentation for both of his knees. The rehabilitation protocol enabled the patient to regain full functionality within six months, with a successful return to work and engagement in low-demand physical activities. This case highlights the importance of considering biological augmentation in the repair of bilateral extensor mechanism ruptures, particularly in patients at high risk of re-rupture, as it may enhance functional outcomes and reduce the need for reintervention.